APPLICATION OF BLENDED LEARNING IN TEACHING AND LEARNING - Kenjaeva Zukhra; Kenjaeva Fotima (American Journals Publishing, 2022)
The present research paper is focused to examine the value of the application of Blended Learning in education as a method for teaching and learning Foreign Languages at university level. The framework took place during the fall semester using 15 students who study at the Academy of the Ministry of Internal Affairs of the Republic of Uzbekistan. In the study, it is used the quantitative techniques for the collection of data and its analysis. It was decided that applying the integration of blended and face to face learning can be effective to setup foreign languages classes.
Keywords: Blended learning, teaching, learning, learning style, autonomous learning, intrinsic motivation, interaction, scaffolding, Moodle platform, collaborative teaching.